2012
DOI: 10.1136/emermed-2011-200966
|View full text |Cite
|
Sign up to set email alerts
|

Major trauma and urban cyclists: physiological status and injury profile

Abstract: Collision with any vehicle can result in death or serious injury to a cyclist. Injury patterns vary with the type of vehicle involved. HGVs were associated with severe injuries and death as a result of uncontrollable haemorrhage. Awareness of this injury profile may aid prehospital management and expedite transfer to MTC care. Rapid haemorrhage control may salvage some, but not all, of these casualties. The need for continued collision prevention strategies and long-term outcome data collection in trauma patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
(29 reference statements)
1
9
0
1
Order By: Relevance
“…Furthermore, only in the case of motor vehicle accidents, the injuries caused by the accident later led to deaths. This finding related to cyclists is supported by many studies [90][91][92][93]. Moreover, most of the cyclist accidents occurred in urban areas because the cyclists collided with trucks and cars.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, only in the case of motor vehicle accidents, the injuries caused by the accident later led to deaths. This finding related to cyclists is supported by many studies [90][91][92][93]. Moreover, most of the cyclist accidents occurred in urban areas because the cyclists collided with trucks and cars.…”
Section: Discussionsupporting
confidence: 63%
“…Frakturer og hodeskader dominerte, men skader i naer sagt alle kroppens organer ble registrert. I likhet med sammenlignbar litteratur fant vi at kollisjonsulykker, spesielt med tyngre kjøretøy, gir størst skadeomfang (14).…”
Section: Eksempler På Skaderunclassified
“…The mere presence of trucks has been shown to contribute to higher accident risk for cyclists [5,6] and truckbicycle accidents usually have more severe consequences for the cyclists involved than any other types of accidents [7][8][9][10]; consequently, trucks are overrepresented in fatal bicycle accidents [11]. According to the EU accident database CARE, 283 cyclist fatalities caused by truck accidents were recorded in 2015 in the EU, which is almost 14% of all cycle fatalities in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…in Denmark, Estonia, Ireland, Slovakia) [12]. Studies of fatal bicycle accidents in London have identified heavy trucks as the most frequently involved vehicle category in accidents resulting in cyclists' deaths over the past two decades [8,13,14].…”
Section: Introductionmentioning
confidence: 99%